Use of Pirina Pretreated with Hydrochloric Acid for the Adsorption of Methyl Violet from Aqueous Solution - Öncel, Mehmet; Güvenç, Ismail; Acemioglu, Bilal (Asian Journal of Chemistry, 2011)
In this study, pirina was used as an adsorbent for the removal of methyl violet from aqueous solution by adsorption technique. The pirina was pretreated with hydrochloric acid before adsorption experiments. Effects of initial dye concentration, temperature and pH on adsorption were investigated as a function of contact time. While the amount of the dye removed by pirina was increasing with increasing contact time, initial dye concentration, solution pH, it decreased with increasing solution temperature. The maximum dye removal were between 82.14 and 97.42 % under all the experimental conditions studied such as concentration, pH and temperature. Furthermore, activated carbon was also used for the adsorption of methyl violet. The maximum experimental amount of dye adsorbed obtained by using activated carbon was 189.30 mg/g per unit adsorbent. Adsorption kinetic and thermodynamic studies were also performed.